2016
DOI: 10.1177/1358863x16676901
|View full text |Cite
|
Sign up to set email alerts
|

Below-knee endovascular interventions have better outcomes compared to open bypass for patients with critical limb ischemia

Abstract: Both open surgery and endovascular peripheral interventions have been shown to effectively improve outcomes in patients with peripheral artery disease, but minimal data exist comparing outcomes performed at and below the knee. The purpose of this study was to compare outcomes following infrageniculate lower extremity open bypass (LEB) versus peripheral vascular intervention (PVI) in patients with critical limb ischemia. Using data from the 2008-2014 Vascular Quality Initiative, 1-year primary patency, major am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
1
22
0
6
Order By: Relevance
“…7 On the other hand, traditional open bypass below the knee is associated with increased perioperative risk with some studies reporting reduced patency rates compared to endovascular intervention. 8 Traditional metallic stents have detrimental effects on vessel physiology. Metallic stents remain in the vessel indefinitely and impair vessel vasomotor tone, remodeling, and autoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…7 On the other hand, traditional open bypass below the knee is associated with increased perioperative risk with some studies reporting reduced patency rates compared to endovascular intervention. 8 Traditional metallic stents have detrimental effects on vessel physiology. Metallic stents remain in the vessel indefinitely and impair vessel vasomotor tone, remodeling, and autoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, which includes a total of 2,566 cases, authors compared the procedures in terms of the rates of 1-year primary patency, major amputation, and mortality, and they found lower 1-year primary patency rate in bypass surgery patients while similar major amputation and mortality rates of both revascularization procedures. 53 Indirect comparisons of endovascular interventions 25,55 and bypass surgery using a venous conduit 56 demonstrated similar outcomes with respect to 1-year limb salvage and mortality rates in the treatment of CLI, both ranging from 85 to 90%, however, a higher requirement of re-interventions following endovascular treatment. 57 This increased rate of re-intervention is associated with an increase in the number of endovascular interventions in case of both intermittent claudication and CLI over the years, which outnumbers the decrease in open surgical procedures.…”
Section: Outcomes Of Comparative Analysis Of Arterial Revascularizatimentioning
confidence: 97%
“…Many comparative studies have been conducted on this issue, and the evidence of whether endovascular or surgical therapy is superior for patients with CLI has been sought for last years. 22,23,[49][50][51][52][53] The first report of the BASIL trial revealed that amputation-free survival and quality-oflife rates were similar in both endovascular and open surgery groups at 6 months. 22 In the long-term, nevertheless, open bypass surgery has provided a significantly increased overall survival benefit of nearly 7 months for patients who survived over 2 years.…”
Section: Outcomes Of Comparative Analysis Of Arterial Revascularizatimentioning
confidence: 99%
“…3,4 However, others suggest that outcomes are similar with both approaches or even superior for PVI. [5][6][7] The discrepancies in these findings are likely reflective of the different populations being studied. Certain patient subgroups have different outcomes after lower extremity revascularization than others.…”
Section: Introductionmentioning
confidence: 98%